Investment opportunities in Central and Eastern European equity markets: an econometric examination of the risk-return relationships for western investors - Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This study focuses on the diversification benefits of the most developed equity markets of Central and Eastern Europe (CEE). To evaluate these benefits of diversification we use so-called spanning tests based on a stochastic discount factor approach and estimated by General Methods of Moments (GMM). Spanning tests investigate whether the returns of test assets (in our case the returns of CEE equity markets) can be mimicked by the returns of some benchmark assets. If this is possible adding the test assets to the set of the benchmark assets does not improve the mean-variance efficient frontier. In recent studies as for example DeSantis (1994), Harvey (1995) or Bekaert/Urias (1996) spanning tests have been successfully applied to emerging equity markets but these studies do not cover the emerging equity markets of Central and Eastern Europe. In addition our study addresses the diversification benefits not only for U.S. investors, as is the usual case in these empirical studies, but extends the analysis on British and German investors, too. A third feature that distinguishes our investigation from most other studies on this topic is the analysis of the effects of currency hedging on diversification benefits. At a quick glance the CEE equity markets seem to offer significant and high diversification benefits. But this picture becomes cloudy after a thorough analysis. Only the equity markets of the Czech Republic, Slovakia and Slovenia contribute significantly to the diversification benefits. But a realisation of these benefits would imply to have not only long but also short positions in CEE equities. Taken into account transaction costs and limited access to futures and options markets it seems to be very doubtful that the theoretical diversification benefits can actually be realised. This result is in correspondence with recent studies on other emerging markets such as DeRoon/Nijman/Werker (2000). The results of the study also show that the home currency of the investor is of some importance for the results of the spanning tests. The outcomes for British, German and U.S. investors are similar but not identical. Therefore it seems to be useful to analyse benefits of diversification not only from the point of view of U.S. investors but to take explicitly into account the currency of the investor. Another interesting result is that currency hedging clearly improves the possible performance of an investment in CEE equity markets. What is now the consequence for investors that consider an investment in CEE equity markets? Our study comes to the result that a buy-and-hold investor could hardly benefit from such an investment. Only investors that have superior timing capabilities could profit from the remarkably strong swings in the levels of CEE equity indices in the past.
Keywords: G15; O16; G12; 330; Spanning Test; Diversification; Emerging Markets; Central and Eastern Europe; Börsenkurs; Aktienmarkt; Kapitalertrag; Risiko; Portfolio-Management; Schätzung; Aufstrebende Märkte; Osteuropa